2023
DOI: 10.1093/rheumatology/kead598
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of bimekizumab in axial spondyloarthritis: a systematic literature review and network meta-analysis

Atul Deodhar,
Pedro M Machado,
Michael Mørup
et al.

Abstract: Objectives To compare the efficacy and safety of bimekizumab 160 mg every 4 weeks, a selective inhibitor of interleukin‑17F and 17A, with biologic/targeted synthetic disease-modifying anti-rheumatic drugs (b/tsDMARDs) in non-radiographic axial spondyloarthritis (nr-axSpA) and ankylosing spondylitis (AS). Methods A systematic literature review identified randomised controlled trials until January 2023 for inclusion in Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…The analyses with BKZ versus IXE 80 mg from COAST-V only (i.e., TNFi-naïve patients) suggested that patients treated with BKZ may have a significantly higher likelihood of achieving greater increases from baseline in SF-36 PCS, however differences observed in 52-week efficacy for all other analyzed outcomes were nonsignificant. These findings are consistent with those from the NMA at weeks 12-16, in which BKZ demonstrated similar relative efficacy versus IXE 80 mg across ASAS outcomes [17,18]. In contrast, analyses comparing BKZ with IXE 80 mg (COAST-V/-W) suggested that patients treated with BKZ may have a significantly higher likelihood of 52-week efficacy across ASAS20, ASAS40, BASDAI change from baseline and SF-36 PCS change from baseline.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The analyses with BKZ versus IXE 80 mg from COAST-V only (i.e., TNFi-naïve patients) suggested that patients treated with BKZ may have a significantly higher likelihood of achieving greater increases from baseline in SF-36 PCS, however differences observed in 52-week efficacy for all other analyzed outcomes were nonsignificant. These findings are consistent with those from the NMA at weeks 12-16, in which BKZ demonstrated similar relative efficacy versus IXE 80 mg across ASAS outcomes [17,18]. In contrast, analyses comparing BKZ with IXE 80 mg (COAST-V/-W) suggested that patients treated with BKZ may have a significantly higher likelihood of 52-week efficacy across ASAS20, ASAS40, BASDAI change from baseline and SF-36 PCS change from baseline.…”
Section: Discussionsupporting
confidence: 81%
“…The analyses of BKZ versus SEC 150 mg (MEASURE 1/2/3/4) provide evidence that patients with r-axSpA treated with BKZ may have a significantly greater likelihood of achieving longer-term ASAS40 response, greater reductions from baseline in BASDAI, and greater increases from baseline in SF-36 PCS. These MAIC results at week 52 are consistent with the NMA analyses at weeks 12-16, in which BKZ achieved higher response rates compared with SEC 150 mg across a range of outcomes in patients with r-axSpA, and provide further evidence supporting the use of BKZ as an effective treatment option in patients with axSpA [17,18]. However, in the separate analyses with BKZ versus SEC 150 mg Fig.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations